VD_FINDINFO Jug / 2013 / 263 vom 14. August 2013 - VD Tribunal cantonal (2013)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, JUGE UNIQUE, CONTRAVENTION, IN DUBIO PRO REO, ACCIDENT DE LA CIRCULATION | 34 al. 3 LCR, 7 al. 3 OCR, 398 al. 4 CPP (CH)